Síntese de bis(indolil)metanos utilizando Fe304 nanoparticulado como um catalisador robusto, eficiente e recuperável magneticamente - Valiati, Stefany (2019)
Herein, we described the synthesis of bis(indolyl)methanes compounds from the FriedelCrafts alkylation reaction between indoles and aldehydes catalyzed by magnetite nanoparticles (nano-Fe3O4). The reactions were performed under solvent-free conditions and at room temperature, and the catalyst was recovered magnetically. This greener methodology developed are simple and efficient, affording the desired bis(indolyl)methanes in good yields (40-99 %) and according to some principles of Green Chemistry, such as: atomic economy, safe synthesis, solvent reduction and auxiliaries, energy efficiency, nonderivative formation, catalysis and safe chemical for the prevention of accidents.